Antimicrobial Activities of Herbal Plant-Dried Chamomile Flowers (Matricaria Chamomilla) Against Different Bacterial Strains (International Journal of Scientific Research in Science and Technology, 2025)
The well-known medical herb chamomile (Matricaria chamomilla), often known as German chamomile, has long been utilized for its antibacterial, anti-inflammatory, and antioxidant qualities. The dried flowers of chamomile include a variety of terpenoids and flavonoids that enhance its medicinal properties. Numerous human conditions, including as hay fever, inflammation, muscular spasms, menstrual problems, sleeplessness, ulcers, wounds, gastrointestinal disorders, rheumatic pain, and hemorrhoids, are frequently treated with chamomile products. Yersinia kritensenii, Staphylococcus aureus, Salmonella, Micrococcus Luteus, Staphylococcus saprophyticus, and Serretia rubidaea were among the bacterial strains against which the antibacterial properties of an aqueous extract of dried chamomile flowers were to be ascertained. During this investigation, the following tests were performed: phytochemical analysis, antibacterial activity, antibiotic susceptibility test (disc diffusion method), and Minimum Inhibitory Concentration (MIC). Numerous phytochemicals, including alkaloids, tannins, coumarins, phenols, flavonoids, glycosides, proteins, and amino acids, have been shown to be present in this herbal extract during phytochemical examination. The study’s findings demonstrated that chamomile extract has antibacterial qualities and can be utilized as an ingredient in a variety of antimicrobial medication formulations.